Case report: Side-firing intraoperative ultrasound guided endoscopic endonasal resection of a clival chordoma - Baker, Katherine E.; Robbins, Austin C.; Kumm, Zeynep T.; Ziemke, Michael K.; Washington, Chad W.; Luzardo, Gustavo D.; Taylor, Charlotte S.; Stringer, Scott P.; Zachariah, Marcus A. (Frontiers in Oncology, 2023)
Clival chordomas are locally invasive midline skull base tumors arising from remnants of the primitive notochord. Intracranial vasculature and cranial nerve involvement of tumors in the paraclival region necessitates image guidance that provides accurate real-time feedback during resection. Several intraoperative image guidance modalities have been introduced as adjuncts to endoscopic endonasal surgery, including stereotactic neuronavigation, intraoperative ultrasound, intraoperative MRI, and intraoperative CT. Gross total resection of chordomas is associated with a lower recurrence rate; therefore, intraoperative imaging may improve long-term outcomes by enhancing the extent of resection. However, among these options, effectiveness and accessibility vary between institutions. We previously published the first use of an end-firing probe in the resection of a clival chordoma. End-firing probes provide a single field of view, primarily limited to depth estimation. In this case report, we discuss the benefits of employing a novel minimally invasive side-firing ultrasound probe as a cost-effective and time-efficient option to navigate the anatomy of the paraclival region and guide endoscopic endonasal resection of a large complex clival chordoma.